Depression in Heart Failure: Psychosomatic Approach - Rudi Putranto (Department of Internal Medicine, Faculty of Medicine Universitas Indonesia-Cipto Mangunkusumo Hospital, 2021)
Depression is a common condition in heart failure (HF) and is considered a risk factor for cardiovascular disease. Depression disorder in patients with heart disease paradigmatically defines a psychosomatic-somatopsychic challenge to any health delivery. However, despite the devastating effects of depression, it is often underdiagnosed and receives little attention in heart failure patients. This review provides an extensive overview of HF regarding epidemiology, disease pathophysiology, diagnosis, and management from the latest literature.